Peran mediasi kepuasan kerja pada pengaruh kepemimpinan Islam terhadap loyalitas karyawan BNI Syariah di Surabaya - Ervina Yusvita Elfani (Journal of Business & Banking, 2019)
Today, sharia banking industry is demanded to provide quality banking services in order to win increasingly tight business competition. For this reason, they need to increase their employees’ loyalty for producing superior performance. Employee loyalty is believed to be influenced by leadership and job satisfaction. This study aims to determine and analyze the effect of Islamic leadership on loyalty mediated by the job satisfaction of Bank BNI Sharia employees in Surabaya. It used a purposive sampling for taking the sample, consisting of 81 BNI Sharia employees in Surabaya. The data were collected through survey method by distributing the questionnaires. Hypothesis testing was conducted using WarpPLS 5.0. It shows that Islamic leadership has no significant effect on employee loyalty. Islamic leadership has a significant effect on job satisfaction. In turn, job satisfaction has a significant effect on employee loyalty. It can be implied that job satisfaction is an important mediating variable for the leaders in order to increase their employee loyalty. The leaders should be able to behave in such a way that they can create employee job satisfaction, their satisfied employees finally become loyal to the company.